Uncertainty as opportunity: the challenge of project based careers. Issue 4 (11th July 2018) - Lloyd-Walker, Beverley; Crawford, Lynn; French, Erica
Abstract : Purpose: Current literature acknowledges the growth of careers in project management. The purpose of this paper is to provide a better understanding of the characteristics of those who choose and continue in project-based careers. Design/methodology/approach: Using social cognitive career theory as the lens to explore project management career journeys, 74 project practitioners were interviewed from across three broad industry sectors. A qualitative research approach was utilized and Atlas.ti was used to analyze and categorize the interview data collected. Findings: Those who choose to continue in project-based roles demonstrate high levels of self-efficacy and coping efficacy and see uncertainty as opportunity. They value challenge, flexibility and variety and take responsibility for their own career progression. Desire for employment security may vary according to personal circumstance. These findings are of value to employers in guiding selection and retention of people for project roles. Research limitations/implications: This is a qualitative and exploratory study covering only three industry sectors and results are not generalizable. SCCT was found useful as a lens for understanding the nature of project-based careers. Practical implications: Findings of this research provide valuable guidance for employers and HR practitioners in project-based organizations. For practitioners the study provides a useful framework for reflecting upon their own careers in projects. Social implications: The nature of careers is changing. Project-based careers are indicative of this change. This study therefore provides insight into an evolving phenomenon. Originality/value: This study expands our understanding of careers in projects, going beyond technical skill development to gain a deeper understanding of personal attributes that contribute to selection into and retention in project-based careers.